Kesiapan Elemen Support, Capacity Dan Value Untuk Pengembangan E-Government Pada Aplikasi â€œMitonâ€ Bagian Administrasi Pembangunan Sekretariat Daerah Timor Tengah Utara Provinsi Nusa Tenggara Timur - Fahik, Aryanto Klau; Akadira, Tora; Jumiati, Ipah Ema (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to determine the extent of readiness for e-government development through the Online Integrated Information Management Application (Miton) in the Development Administration Section of the North Central Timor Regional Secretariat, East Nusa Tenggara Province. The problem focuses on 3 (three) important elements of e-Government Development, namely Support Elements, Capacity Elements, and Value Elements based on). To approach this problem, a theoretical reference from Indrajit, and an opinion from Indrajit (Indrajit 2016) was used. Data was collected through questionnaires and analyzed quantitatively. This study concluded that the average level of readiness of 3 (three) elements of successful e-government development in the Miton application it is 75.5% with the details of each element being as follows: (1) Support Elements are ready at 78.59%, (2) Capacity Elements are ready at 70.75%, (3) Value Elements are ready at 70.75% 77.14 %